PERANAN VISUM ET REPERTUM PADA TAHAP PENYIDIKAN DALAM MENGUNGKAP TINDAK PIDANA PEMERKOSAAN - Erdian Cahya (Journal of Law ( Jurnal Ilmu Hukum ), 2013)
ABSTRACTVisum Et Repertum role in the criminal proceedings is very important, especially in resolving matters relating to the soul or body of a person , given the judges , prosecutors and lawyers only legally be able to master . Vise as documentary evidence, as well as other evidence which in article 184 Criminal Procedure Code that are not binding on the judge . This is consistent with the negative evidence in criminal procedural law adopted in Indonesia , where the element of conviction the judge plays an important role in the process of resolving a criminal case.Visum Et Repertum role as documentary evidence help the public prosecutor in making the demands that will be put forward upfront trial. Because in Visum Et Repertum it contained or contains the information of a doctor and a description of what is seen and found on examination of evidence and can be used as a material consideration in decisions of judges .